Just-in-time math for engineers - Fripp, Archibald L. (Newnes, 2003)
Just-In-Time Math is a concise review and summary of the mathematical principles needed by all engineering professionals. Topics covered include differential calculus, integral calculus, complex numbers, differential equations, engineering statistics, and partial derivatives. Numerous example engineering problems are included to show readers how to apply mathematical techniques to a wide range of engineering situations. This is the perfect mathematics refresher for engineering professionals who use such math-intensive techniques as digital signal processing. *Provides complete coverage of mathematical tools and techniques most commonly used by today's engineers *Includes conversion tables, quick reference guides, and hundreds of solved example problems based on common engineering situations *Accompanying CD includes engineering calculators and an electronic version of the book.